LEGALITAS DAN PERLINDUNGAN HUKUM DALAM PERKAWINAN TIDAK TERCATAT DI INDONESIA : ANALISIS YURIDIS NORMATIF DAN IMPLIKASI SOSIOLOGIS - Irfanul Faruqi (CV. Denasya Smart Publisher, 2026)
Unregistered marriages (nikah siri) remain a prevalent phenomenon in Indonesia, despite positive law requiring every marriage to be officially registered with the competent authority. This study aims to analyze the legality and legal protection of unregistered marriages, as well as the legal status and inheritance rights of children born from such unions under Indonesian law.The research employs a normative juridical method with a statutory and conceptual approach, examining Law Number 1 of 1974 on Marriage and its amendments, the Compilation of Islamic Law, Constitutional Court Decision Number 46/PUU-VIII/2010, and various relevant legal literature. The findings indicate that unregistered marriages may be considered religiously valid if they fulfill the pillars and requirements of marriage; however, they do not obtain administrative legal recognition due to the absence of official registration. This condition gives rise to various legal issues, particularly affecting women and children, including weak protection of rights related to maintenance, marital property, the legal status of children, and inheritance rights. Constitutional Court Decision Number 46/PUU-VIII/2010 represents a significant development by recognizing the civil relationship between children born out of wedlock and their biological fathers, provided it can be legally proven. Additionally, the mechanism of isbat nikah serves as a legal solution to obtain marriage legality and legal certainty for families. This study concludes that marriage registration plays a crucial role in ensuring legal protection, certainty of legal status, and the fulfillment of civil rights of husbands, wives, and children within the Indonesian legal system.